2007
DOI: 10.1161/01.res.0000260180.42709.29
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Deficiency Increases Cerebral Ischemic Injury

Abstract: Abstract-Caveolins (Cav), the principal structural proteins of the caveolar domains, have been implicated in the pathogenesis of ischemic injury. Indeed, changes in caveolin expression and localization have been reported in renal and myocardial ischemia. Genetic ablation of the Cav-1 gene in mice was further shown to increase the extent of ischemic injury in a model of hindlimb ischemia. However, the role of Cav-1 in the pathogenesis of cerebral ischemia remains unknown. Immunoblot and immunofluorescence analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 35 publications
7
128
2
Order By: Relevance
“…These results extend those that have shown that the loss of Cav-1, either through siRNA or transgenic models, can blunt neuroprotection (9) and metabotropic glutamate receptor-mediated long-term depression (43,59) and accelerate a neurodegenerative phenotype (32,60,61). Our findings obtained with siRNA-mediated Cav-1 knockdown extend the role of Cav-1 in neuronal signaling to a variety of receptors in addition to glutamate.…”
Section: Syncav1supporting
confidence: 88%
“…These results extend those that have shown that the loss of Cav-1, either through siRNA or transgenic models, can blunt neuroprotection (9) and metabotropic glutamate receptor-mediated long-term depression (43,59) and accelerate a neurodegenerative phenotype (32,60,61). Our findings obtained with siRNA-mediated Cav-1 knockdown extend the role of Cav-1 in neuronal signaling to a variety of receptors in addition to glutamate.…”
Section: Syncav1supporting
confidence: 88%
“…Consistent with our findings (Figures 6 and 7), Griffoni et al 26 reported that knockdown of caveolin-1 by antisense oligonucleotides impaired angiogenesis, both in vitro in a fibrin gel assay and in vivo on chicken chorio-allantoic membranes. In addition, Jasmin et al 59 found that ischemic cerebral injury generated an impaired angiogenic response in cav-1 Ϫ/Ϫ mice, and Woodman et al 22 reported decreased angiogenesis induced by basic fibroblast growth factor in Matrigel plugs, and, as reported here (Figure 7), decreased B16 tumor growth and associated angiogenesis. On the other hand, Bauer et al 23 found that angiogenesis induced by Ad-VEGF 164 and by tissue ischemia was significantly impaired in transgenic mice in which caveolin-1 was overexpressed.…”
Section: Discussionsupporting
confidence: 71%
“…Decreased angiogenesis was shown using bFGF-containing matrigel plugs, 20 VEGF-expressing adenoviral vector, 22 experimental colitis 23 or cerebral ischemia. 37 Reduced ischemic hindlimb reperfusion after femoral artery resection is also apparent in these mice. 21 Defective mobilization of endothelial progenitors in response to ischemia was further documented in caveolin-1-deficient mice.…”
Section: Discussionmentioning
confidence: 87%